The novel adjuvant dmLT promotes dose sparing, mucosal immunity and longevity of antibody responses to the inactivated polio vaccine in a murine model. Issue 16 (15th April 2015) - Norton, Elizabeth B.; Bauer, David L.; Weldon, William C.; Oberste, M. Steven; Lawson, Louise B.; Clements, John D.
Highlights: We evaluated the adjuvant dmLT admixed with inactivated poliovirus vaccine (IPV). Fractional IPV doses were delivered intramuscularly or intradermally in mice. dmLT adjuvant enables dose-sparing of IPV, particularly for serotype-1. dmLT enhances mucosal immunity and longevity of serum anti-PV neutralizing titers. Abstract: One option for achieving global polio eradication is to replace the oral poliovirus vaccine (OPV), which has the risk of reversion to wild-type virulence, with the inactivated poliovirus vaccine (IPV) vaccine. Adjuvants and alternate routes of immunization are promising options that may reduce antigen dose in IPV vaccinations, potentially allowing dose sparing and cost savings. Use of adjuvants and alternate routes of immunization could also help promote mucosal immunity, potentially mimicking the protection against intestinal virus shedding seen with OPV. In the current study, we examined the impact of combining the novel adjuvant dmLT with trivalent IPV for dose sparing, induction of mucosal immunity and increasing longevity of anti-poliovirus (PV) responses in a mouse model following either intradermal (ID) or intramuscular (IM) delivery. We found that non-adjuvanted ID delivery was not superior to IM delivery for fractional dose sparing, but was associated with development of mucosal immunity. Vaccination with IPV + dmLT promoted serum anti-PV neutralizing antibodies with fractional IPV doses by either IM or ID delivery, achieving at least five-fold dose sparing above non-adjuvanted fractional doses. These responses were most noticeable with the PV1 component of the trivalent vaccine. dmLT also promoted germinal center formation and longevity of serum anti-PV neutralizing titers. Lastly, dmLT enhanced mucosal immunity, as defined by fecal and intestinal anti-PV IgA secretion, when included in IPV immunization by ID or IM delivery. These studies demonstrate that dmLT is an effective adjuvant for either IM or ID delivery of IPV. Inclusion of dmLT in IPV immunizations allows antigen dose sparing and enhances mucosal immunity and longevity of anti-PV responses.